Penerapan Trauma Healing untuk Mengatasi Kecemasan Pasca Banjir: Application of Trauma Healing to Overcome Post-Flood Anxiety - Akhmad Sugianto; Sri Alvie Maulidiyawati; Syarifah Syarifah; Syarwani Hadi; Yuda Yuda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Community service carried out in Hantakan village, Hantakan sub-district, Hulu Sungai Tengah district, is in the form of assisting students together with the community in formulating innovative and participatory planning formulations and policies for trauma healing applications to overcome post-flood anxiety, in which the main target of this trauma healing activity is children in the local village. The purpose of trauma healing activities carried out by students for children is to reduce the level of anxiety and restore the emotional condition of children after the disaster to help the spirit return to the way it was before the disaster occurred with various kinds of games that were carried out both individually and in groups as well as gifts. Material that aims to improve the characteristics of the child. The stages of trauma healing implementation carried out by these students include: a). Initial Stage, b). Core Stage, c). Monitoring and Evaluation Phase. Implementing trauma healing using the Participatory Rapid Appraisal (PRA) method or participatory village assessments carried out through various activities such as observations, surveys, and interviews.